Technological resources to teach English vocabulary to children with dyslexia; the case of students at 9th year of Educación Básica, “Unidad Educativa Santo Tomás Apóstol Riobamba” in Chimborazo province, Riobamba city, period 2021-2022 - Caizapanta García, Lucía Emilia (2022)
Dyslexia in education has been visibly noticed in recent years, so that educational units and institutions are becoming more present with possible solutions and help for students who need special attention to their needs, hence the concern and curiosity of how these difficulties are solved. The main objective is to analyze the technological resources used to teach vocabulary to students with dyslexia. The research is conducted using a qualitative approach, which helps us to identify and obtain the perspective of participants with dyslexia to acquire information and knowledge through technological resources. It also adopts an interpretive paradigm that helps us to seek assumptions about the process of teaching vocabulary to students with dyslexia and how technological resources are used to that goal, the research is non-experimental, so the situation is observed in its natural context without any intervention by the researcher. The type of research used was exploratory since it was necessary to investigate the problem and check its reliability by means of an observation instrument which revealed the specific points between dyslexia and the teaching of vocabulary with technological resources in ninth grade students. The observation guide showed us the difficulties that students with dyslexia present in the classroom and how they affect their learning, since they have several symptoms that must be assessed in time, however the application of technological resources in teaching helped the significant progress of vocabulary learning of students, making them feel more comfortable when learning, since teachers relied on their learning styles to solve or minimize student setbacks. We conclude the research by emphasizing the importance of the correct use of technological resources and strategies closely linked to the learning of new vocabulary, focusing on the learning styles of each student with dyslexia.